Global creative architecture : selected works of world architects - Schulz, Daniel (Barcelona, Spain : Links International, 2007)
This collection brings together buildings that inject a fresh dose of creativity into any architectural project and set the tone and pace for architects around the world, surveying the range of different styles, functions and needs that make each project a unique challenge. Along with the iconic, definitive buildings of the era are lesser-known projects that are no less creative or surprising.
Includes index.
Keywords: Architecture, Modern -- 21st century -- Pictorial works; Architecture, Modern -- 21st century -- Designs and plans